Analisis Menggunakan Metode Pembobotan Untuk Penyusunan Peta Ketahanan Pangan & Penanggulangan Kerentanan Pangan Di Kecamatan Celala - S, Richasanty Septima; Syahputra, Hendri; Maulida, Emy (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Mapping of food security in celala sub-district has not been mapped into the Geographic Information System (GIS). Food security is a condition where humans can meet their food needs. Therefore, as a first step to overcome the problem of food insecurity, efforts are needed regarding the condition of food security in Celala District. Information on food security and insecurity is important to provide information to decision makers in making programs and policies, this information can be used as a an instrument to deal with food crises in the context of efforts to protect/avoid food and nutrition crises in the short, medium and long term.